Hubungan Status Gizi dengan Prestasi Belajar - Muhamad Ariq Fauzan; Yesi Nurmalasari; Anggunan Anggunan (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; One of the factors that can affect children's learning achievement is nutritional status. The low nutritional status of children will have a negative impact on improving the quality of human resources. Aim; know the nutritional status of children, learning achievement, and the relationship between nutritional status and learning achievement. Method; Research design with an observational analytic approach with cross-sectional design. The sampling technique used the total sampling method. Data analysis used the Spearman Rank correlation test. Result; that the frequency distribution of children's learning achievement, most of the respondents had good learning achievement, namely as many as 55 people with a percentage (71.4.0%), the frequency distribution of children's nutritional status, most of the respondents had normal nutritional status, namely 54 (70.1%) and there is a significant relationship between nutritional status and learning achievement in children. Conclusion: that there is a significant relationship between nutritional status and children's learning achievement